Diversity of membrane transport proteins for vitamins in bacteria and archaea - Jaehme, Michael; Slotboom, Dirk Jan (Biochimica et biophysica acta, 2015)
All organisms use cofactors to extend the catalytic capacities of proteins. Many bacteria and archaea can synthesize cofactors from primary metabolites, but there are also prokaryotes that do not have the complete biosynthetic pathways for all essential cofactors. These organisms are dependent on the uptake of cofactors, or at least their precursors that cannot be synthesized, from the environment. Even in those organisms that contain complete biosynthetic pathways membrane transporters are usually present, because the synthesis of cofactors is more costly than uptake. Here we give an overview of bacterial and archaeal transport systems for B-type vitamins, which are either cofactors or precursors thereof. Prokaryotic vitamin transporters are extremely diverse, and found in many families of transporters. A few of these transport systems have been characterized in detail, but for most of them mechanistic insight is lacking. The lack of structural and functional understanding of bacterial vitamin transporters is unfortunate because they may be targets for new antibiotics. This article is part of a Special Issue entitled Structural biochemistry and biophysics of membrane proteins. Guest Editor: Bjorn Pedersen. •Bacteria and archaea use diverse families of transport proteins for vitamin uptake.•Genome analysis has accelerated the identification of vitamin transporters.•Vitamin transport by prokaryotes has potential medical and biotechnological relevance.